A formal definition for translating XML documents to the entity relationship model. (10th September 2007) - Bagui, Sikha
In this paper we propose to conceptually model XML data and documents to the ER model. We present a set of rules for converting XML documents and their data to the ER model. This conceptual view of the XML data can then be easily translated to the relational model, which will then open the way for the development of applications that exploit well known reliable relational technologies to manage and manipulate large collections of XML documents and data travelling through the web.